Unlocking the Influence of Digital Marketing Strategies on Startup Performance: A Case Study in Bangladesh - Md. Rishad Kabir (Journal of Information Systems and Informatics)
This study investigates the impact of different digital marketing tools on the growth and sustainability of startups in Rangpur City, Bangladesh. With the proliferation of digital technology, entrepreneurs in Rangpur are increasingly employing strategies such as social media marketing, search engine optimization (SEO), e-mail marketing, and social networking to augment their exposure and compete in local and global markets. The research aims to analyze different digital marketing methods, and identify challenges that impacts on business performance in Rangpur city. A survey of 132 startup entrepreneurs and business professionals indicates that digital marketing, mainly social media marketing and social networking, substantially impacts business success by explaining 75.3% of the variance in performance outcomes. The findings suggest enterprises with less than 10 years of Operation should emphasize digital marketing specifically social media marketing to leverage the expanding digital trend, particularly in the restaurant, retail, and textile industries. Despite its diminished effectiveness, e-mail marketing continues to be a technique that warrants optimization. The findings offer substantial insights for entrepreneurs, marketers, and policymakers, emphasizing the essential function of digital marketing in facilitating corporate growth and economic development in emerging countries like Bangladesh. This study contributes to the existing literature by highlighting the importance of digital marketing tools for startups in growing regions like Rangpur City. It provides practical recommendations for enhancing digital marketing tactics to promote business success and growth.